Biophysiology of in ovo administered bioactive substances to improve gastrointestinal tract development, mucosal immunity, and microbiota in broiler chicks - Ayalew, Habtamu; Wang, Jing; Wu, Shugeng; Qiu, Kai; Tekeste, Ayalsew; Xu, Changchun; Lamesgen, Dessalegn; Cao, Sumei; Qi, Guanghai; Zhang, Haijun (Poultry science, 2023)
Early embryonic exogenous feeding of bioactive substances is a topic of interest in poultry production, potentially improving gastrointestinal tract (GIT) development, stimulating immunization, and maximizing the protection capability of newly hatched chicks. However, the biophysiological actions and effects of in ovo administered bioactive substances are inconsistent or not fully understood. Thus, this paper summarizes the functional effects of bioactive substances and their interaction merits to augment GIT development, the immune system, and microbial homeostasis in newly hatched chicks. Prebiotics, probiotics, and synbiotics are potential bioactive substances that have been administered in embryonic eggs. Their biological effects are enhanced by a variety of mechanisms, including the production of antimicrobial peptides and antibiotic responses, regulation of T lymphocyte numbers and immune-related genes in either up- or downregulation fashion, and enhancement of macrophage phagocytic capacity. These actions occur directly through the interaction with immune cell receptors, stimulation of endocytosis, and phagocytosis. The underlying mechanisms of bioactive substance activity are multifaceted, enhancing GIT development, and improving both the innate and adaptive immune systems. Thus summarizing these modes of action of prebiotics, probiotics and synbiotics can result in more informed decisions and also provides baseline for further research.